Formulation and Physical Evaluation of Depilatory Cream from with Variation Concentrations of Turmeric (Curcuma longa) and Bromelain Enzyme - Diah Ratnasari; Janatun Na’imah; Nastiti Trikurniadewi; Irani Agustin; Danu Prastiyo (LPPM Universitas Harapan Bangsa, 2025)
The Indonesian cosmetics industry market is predicted to grow by 5.91% per year, including skin care products. One type of skin care is removing unwanted hair from the skin because this hair can interfere with appearance, especially for women. One way to remove this hair is by using hair removal cream (depilatory cream). One natural ingredient that has depilatory properties is turmeric. Depilatory cream also requires sulfhydryl protease enzymes that can break down the molecular structure of proteins contained in hair into amino acids. One protease enzyme is bromelain. The purpose of this study was to obtain the best formula for depilatory cream with varying levels of turmeric and bromelain enzymes based on physical evaluation results. The research method used was experimental research with stages of turmeric extraction, bromelain enzyme isolation, depilatory cream formulation, and physical evaluation of the depilatory cream. The results showed that Formula 1 was the best turmeric-based depilatory cream formula with bromelain enzyme based on physical evaluation results.